Reproductive aspects of systemic lupus erythematosus. (September 2016) - Oktem, Ozgur; Yagmur, Hande; Bengisu, Hale; Urman, Bulent
Highlights: This review article provides an update on multi-faceted roles of estrogen hormone in both normal immune function and auto-immunity. It reviews the ovarian function and other poor reproductive outcomes in young females with SLE. Gonadotoxic potentials of the immunosuppresive therapies are discussed. Fertility preservation options are provided in young females who are diagnosed with SLE. Abstract: Systemic lupus erythematosus (SLE) is an auto-immune systemic disease showing a strong predilection for women of reproductive age. Higher prevalance of SLE among young women are in part accounted for by the effects of estrogen hormone on immune system. The key pathophysiological features of this disease are the generation of autoantibodies and the deposition of antibody-antigen complexes in the basal membranes of the organs where they evoke inflammatory responses and injury. Young females diagnosed with SLE are more prone to developing a multitude of adverse reproductive and obstetric outcomes, especially in the presence of active disease. Our motivation in writing this review article is to outline the recent interesting findings of molecular and clinical studies showing multi-faceted roles of estrogen hormone in both normal immune function and auto-immunity and to provide an update on the ovarian function and other poor reproductive outcomes in young females with SLE.